Migration and Freedom of Movement of Workers: EU Law, Crisis and the Cypriot States of Exception - Nicos Trimikliniotis (Laws, 2013)
This paper examines the authoritarian immigration policy of the Republic of Cyprus (RoC), which often results in the denial of the rights of migrants, TCNs, and EUNs. It examines how the mode of immigration control is connected to the particular state of exception in Cyprus known as ‘the doctrine of necessity’. It focuses particularly the issue of criminalizing, detention and expulsion of migrants, both TCNs and EUNs and the denial of residency rights for TCNs. The paper introduces the basic components towards an analytical frame for understanding and critiquing the current legal framework. Repressive migration control is a manifestation of an ill-construed conception of ‘sovereignty’ in a divided country, which the State seeks to justify on the grounds of ‘necessity’ and ‘exception’. In addition, the RoC is currently facing the banking/economic crisis and mass unemployment, which has provided a fertile ground for racism and xenophobia. The paper concludes with some ideas about the alternative policies ahead. Important for this paper are the current global and European debates around the ‘states of exception’, ‘emergency’, ‘necessity’, and ‘sovereignty’ in the context of the dissensus or fundamental disagreement over the issue migration and the racialization of subaltern migrants. The case of Cyprus is discussed, in part as an exception, but also as a particular instance of a broader global and European issue.